2008
DOI: 10.4067/s0716-10182008000600001
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de antimicrobianos parenterales en diferentes hospitales de Chile durante el año 2005

Abstract: Intravenous antimicrobial use among different hospital in Chile during 2005Intravenous antimicrobial consumption has not been evaluated previously in Chile. In order to know this consumption (in DDD per 100 bed days), associated factors and antimicrobial control systems across the country, a questionnaire was sent to evaluate these features during 2005. A total of 29 public hospitals and private clinics answered this poll, 20 belonging to the public health system (69%). Only 48.1% declared to have an independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…En los hospitales las infecciones son cada día más difíciles de tratar por lo que un número elevado de pacientes recibe tratamiento con AB (Angles, 2018;Fica, 2008;Vega et al, 2015). Además, se ha observado que la mitad de las prescripciones son inadecuadas, que el consumo es elevado y su uso irracional; lo que ha contribuido a que existan altas tasas de resistencia bacteriana (Fleming-Dutra et al, 2016;Nathwani et al, 2019).…”
Section: Introductionunclassified
“…En los hospitales las infecciones son cada día más difíciles de tratar por lo que un número elevado de pacientes recibe tratamiento con AB (Angles, 2018;Fica, 2008;Vega et al, 2015). Además, se ha observado que la mitad de las prescripciones son inadecuadas, que el consumo es elevado y su uso irracional; lo que ha contribuido a que existan altas tasas de resistencia bacteriana (Fleming-Dutra et al, 2016;Nathwani et al, 2019).…”
Section: Introductionunclassified
“…En nuestro país, para el año 2008 ceftriaxona fue el AM más consumido en el medio hospitalario, representando diariamente cerca de 18 tratamientos por cada 100 camas ocupadas. Ciprofloxacina registró valores promedio de 0,68 DDD/100 día/cama 23 . En nuestro centro, el año 2013 el consumo de ceftriaxona fue de 8,4 DDD/100 días cama, mientras que ciprofloxacina y levofloxacina fueron de 2,54 y 1,86 DDD/100 camas día respectivamente.…”
unclassified
“…5 unidad Bioestadística. 6 A ntimicrobial control is imperative due to emergence of resistant isolates, shortage of therapeutic drugs, risk of clinical failure and mortality, and expenditure increases 1,2 . Recently, a global program has been issued by WHO asking to adopt different strategies to control this threat 3 .…”
mentioning
confidence: 99%
“…These interventions require financial investment to hire human resources, and support differente activities. Chile has a governmental regulation issued by the Ministry of Health since 1999 in order to implement antimicrobial stewardship programs (ASP) in hospitals that has never been supervised, and studies developed more a decade ago showed partial fulfillment 6 . Literature on the impact of ASP in Chile is scarce 7,8 and probably explained by the low number and the geographically concentrated distribution of infectious diseases (ID) specialists.…”
mentioning
confidence: 99%